THE IMPORTANCE OF A GENDER PERSPECTIVE IN LEISURE PSYCHOLOGY - Sánchez-Herrero Arbide, Silvia (Anales de Psicología / Annals of Psychology, 2008)
In the last years, the need of a gender perspective in different areas of study of the human being is arising as a subject of great importance. Psychology is not unaware to this fact, and the temporal devotion of different spheres of life and the use of free time in men and women are taking shape as a subject of vital prevalence with economic, working, personal and, social consequences. To be in mind this gender perspective in the study of leisure is a vital tool to understand the lifestyles of women and men, the work life balance and the impact that those aspects have in the physical and mental health of people.